"Behold, there is a New Man born!": Understanding the Short-lived Optimism about Australia's First Generation of "Native-born" White Men. (June 2014) - Downing, Karen
Contemporary accounts of the first generation of white men born in Australia seemed to describe them as physically superior to their British counterparts. Social and economic historians provide evidence that they were indeed taller and explain the phenomenon in terms of diet and living standards. This article suggests that contemporary observations also reflected the eighteenth-century British concerns that "civilized" life in Britain threatened the essential nature of men. Popular medical literature highlighted the problems, emigration was promoted as the solution, and men's personal writings reveal that they understood and acted on these messages. The physical superiority of Australia's firstborn white men was not unexpected. But the short-lived optimism around these "new" men highlights ongoing tensions between men and modernity.